2019
DOI: 10.1002/celc.201900725
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical CO2 Reduction on Bimetallic Surface Alloys: Enhanced Selectivity to CO for Co/Au(110) and to H2 for Sn/Au(110)

Abstract: We investigated electrochemical CO2 reduction (ECR) on 0.1 monolayer‐thick‐Co and Sn‐deposited Au(110) surfaces (Co/Au(110), and Sn/Au(110)). Scanning tunneling microscopic images showed quasi‐one‐dimensional Co and Sn islands with different aspect ratios growing along the trenches of the missing‐row direction of the (1×2) reconstructed Au(110) surface. The selectivity and partial current density of the CO and H2 evolutions correlated with those of the deposited metals. CO evolution selectivity of the former C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
(87 reference statements)
0
12
0
Order By: Relevance
“…This study cannot explain the origin of large difference in potential-dependent selectivity at only a 10% difference in composition. Elucidating this composition effect is challenging for nanostructured catalysts because the selectivity is also influenced by several factors including the surface atomic structures 12,13,53 and lattice strain. 54,55 Studies using model catalysts such as single-crystal electrodes with well-defined surface structures can be a potential tool for clarifying this issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study cannot explain the origin of large difference in potential-dependent selectivity at only a 10% difference in composition. Elucidating this composition effect is challenging for nanostructured catalysts because the selectivity is also influenced by several factors including the surface atomic structures 12,13,53 and lattice strain. 54,55 Studies using model catalysts such as single-crystal electrodes with well-defined surface structures can be a potential tool for clarifying this issue.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement of activity and selectivity for CO 2 RR electrocatalysts has been studied by various approaches, such as surface structure control, [11][12][13] halogen anion additions, 14,15 and surface modification by organic molecules. 7,16,17 In addition, alloying is an effective strategy to improve the CO 2 RR properties.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Previous research has shown that Au, Ag, and Zn electrodes selectively convert CO 2 to CO. 8 In particular, Au showed relatively high efficiency for CO 2 reduction compared to that for hydrogen evolution, which is a competitive reaction of CO 2 reduction in aqueous solutions. [8][9][10] However, the activity and selectivity of the Au electrode for converting CO 2 to CO remain insufficient for widespread application, and further research on CO 2 electrolysis systems is necessary to attain industrialisation.…”
mentioning
confidence: 99%
“…To date, the main catalysts used in the electrocatalytic CO 2 RR of CO 2 to CO include noble metals (Au, Ag, and Pd), 13–15 oxides (CuO, ZnO, and Bi 2 O 3 ), 16–18 chalcogenides (Cu 2 S, CdS, and MoS 2 ), 19–21 alloys (Pd–Ag, Co–Au, and Cu–Ru), 22–24 single-atom catalysts 25–28 and some carbon materials. 29–31 These catalysis processes can efficiently hinder the hydrogen evolution reaction (HER), which is competitive with CO 2 RR.…”
mentioning
confidence: 99%